Role of Nurses in Prevention and Management of Inappropriate Medication Use in Older Adults - ทิพย์กาญจนเรขา กฤษณาพร; สาลีกุล สำลี (Journal of The Royal Thai Army Nurses, 2019)
Thailand is entering the ageing society perfectly in 2018. It is imperative that the government and all relevant agencies prepare for the aging society. Because, the older adults are considered to be at high risk for various diseases, especially chronic diseases. Older people with chronic diseases have the highest proportion use medicine when compared to other age groups. The purpose of the drug is to prevent or treat the disease, but at the same time the medication may be effective. Including inappropriate medication use in the older adults. These problems are common because of the use of various medication and age-related physiologic changes. Inappropriate use of antipsychotics in older adults has a greater prevalence of problems. Nurse is one of the health team members who play an important role in preventing problems related to the use of illicit drugs in the older adults. Also, care should be taken if there are any problems that make older people at risk or dangerous. Nurses need to have relevant knowledge to help them effectively prevent and deal with the problem. This article aims to present knowledge consist of appropriate use of drugs in the older adults, the older adults with drugs use, Age-related change of the older adults affects the drug use, problems related to drug use in the older adults, drug use behavior for the older adults, and Nursing role in preventing and dealing with inappropriate drug use in the older adults.